CONSERVATIVE APPROACH TO DEEP CARIES LESIONS MANAGEMENT IN CHILDREN - N.V. Yanko (Ukrainian Medical Stomatological Academy, 2019)
The aim of the study was to systematize effective deep caries management methods in children in order to determine the indications for their use. The author used Google search engine to find articles and scientific publications published between 2006 and 2019. Reversible pulpitis is an indication for applying the methods preserving pulp vitality performed under aseptic and antiseptic conditions, provided the absence of decompensated form of caries and chronic somatic pathology. To prevent the accidental pulp exposure, it is better to use a partial excavation of the affected dentin followed by an indirect pulp capping. During direct pulp capping and pulpotomy the bleeding should be arrested within 3-5 min in primary teeth and within 5 min - in permanent ones. Direct pulp capping with MTA is indicated at the spot pulp exposure in permanent teeth, the use of this method in the primary teeth requires further research. Direct pulp capping with 5.25% sodium hypochlorite used as a hemostatic agent and MTA-type cement application under endodontic microscope or pulpotomy with MTA or Biodentine can be applied when treating reversible pulpitis in permanent teeth. In asymptomatic temporary teeth affected by reversible pulpitis full pulpotomy is adviced which is more effective with MTA. A promising direction in deep caries management research is direct and indirect pulp capping of primary teeth with Biodentine.